Case report: Severe nonketotic hyperglycinemia in a neonate without apparent seizures but concomitant cleft palate and cerebral sinovenous thrombosis - Thewamit, Rapeepat; Khongkhatithum, Chaiyos; Thampratankul, Lunliya; Kamolvisit, Wuttichart; Khongkrapan, Arthaporn; Wattanasirichaigoon, Duangrurdee (Frontiers in Pediatrics, 2023)
Nonketotic hyperglycinemia (NKH) is in most cases a fatal inborn error of metabolism which usually presents during the neonatal period as encephalopathy and refractory seizures. The reported congenital anomalies associated with NKH included corpus callosal agenesis, club foot, cleft palate, and congenital heart disease. Here we report a newborn who presented with encephalopathy without overt seizures, cerebral venous sinus thrombosis and cleft palate. Electroencephalography showed a burst suppression pattern, which suggests the etiology could be due to a metabolic or genetic disorder. The amino acid analysis of plasma and cerebrospinal fluid showed elevated glycine. Whole exome sequencing identified a heterozygous c.492C>G; p.Tyr164Ter variant in exon 4 of the GLDC gene inherited from patient’s father. Further long-read whole genome sequencing revealed an exon 1-2 deletion in GLDC gene inherited from patient’s mother. Additional analyses revealed no pathogenic variants of the cleft palate-related genes. The cleft palate may be an associated congenital anomaly in NKH. Regarding cerebral venous sinus thrombosis, we found heterozygous variant (p.Arg189Trp) of the PROC gene, which is a common cause of thrombophilia among Thai newborns. A neonate with NKH could present with severe encephalopathy without seizures. A close follow up for clinical changes and further next generation sequencing are crucial in definite diagnosis for neonates with encephalopathy of unclear cause.